Gamification in Early Childhood Education: Boosting Engagement and Learning Outcomes - Yusuf Kareem; Omar Zayd Khalid (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Gamification—the use of game mechanics in non-gaming contexts—has proven to be an effective tool for enhancing children's learning experiences. This paper examines how gamified learning platforms influence early childhood education by improving motivation, attention span, and knowledge retention. The study evaluates the effectiveness of various educational games and proposes best practices for implementing gamification in preschool and primary education.